High-quality genome assembly and annotation of the pacu Piaractus mesopotamicus: an aquatic genetic resource of South American aquaculture - Mascali, Florencia Carla; Mastrochirico-Filho, Vito Antonio [UNESP]; Posner, Victoria María; Rubiolo, Juan Andrés; Hashimoto, Diogo Teruo [UNESP]; Villanova, Gabriela Vanina (Springer Nature, 2024)
Piaractus mesopotamicus, popularly known as pacu, is a freshwater fish native to the Paraguay-Paraná River basin of South America. This species has been historically exploited by commercial fishermen, and nowadays, it is very important for aquaculture in many countries of South America. Good quality meat and excellent adaptability to culture systems are some of its remarkable farming features. To support studies into the biology, genetics, and genomics of the pacu, we have produced the first high-quality chromosome-scale genome for P. mesopotamicus. A 1.28 Gbp genome containing 27 linkage groups has been obtained by integrating HiFi PacBio reads, and SNP linkage map data developed in this work. The proportion of BUSCO genes identified was near 98%, a value that positions this assembly as one of the highest-quality genomes available for Neotropical fish. Furthermore, genome annotation of genes, repetitions, and non-coding transcripts were performed. Comparison with the genome of the related species Colossoma macropomum showed a high level of synteny, which gives important information regarding the origin of both species and for hybrid management. A broader comparison showed the phylogenetic relationship between pacu and related Characiformes species as well the presence of groups of ortholog proteins. Moreover, specific pacu proteins were identified as well as their functional description and their own metabolic pathways, which may be useful for pacu aquaculture. The high-quality genome assembled in this work and its annotation provide a valuable genomic resource for future studies, and they are a helpful resource for pacu aquaculture.
Keywords: Chromosome-scale genome assembly; HiFi reads; Pacu; SNP linkage map